Determination of \(γ\)-rays Relative Intensities from the \(^35\)Cl\((n, γ )^36Cl\) Reaction on Filtered Thermal Neutron Beam - Anh, Tran Tuan; Son, Pham Ngoc; Tan, Vuong Huu (Communications in Physics, 2016)
The relative intensities of prompt g-rays from the 35Cl(n, g)36Cl reation with thermal neutron have been used as secondary g-ray intensity standards for the prompt gamma neutron activation analysis (PGNAA) and for nuclear data measurements due to a high capture cross section. The filter neutron technique was applied for producing a thermal neutron beam at the neutron channel No. 4 of the Dalat nuclear research reactor. The neutron flux and Cd-ratio are 8.72 ´ 106 n.cm-2.s-1and 134, respectively, determined by the gold foil activation method. A new PGNAA system with a HPGe detector of 58% relative efficiency and a digital spectrometer was used to detect prompt gamma rays from the 35Cl(n, g)36Cl reaction. In this work, relative intensities of 23 prompt g-rays have been determined on the filtered thermal neutron beam. The present results within accuracy 3.0% or better are in good agreement with literature values and data from previous measurements.